A novel linear matrix method to analyze adhesive joints. (15th October 2019) - Areiza-Hurtado, Mauricio; Vega-Posada, Carlos A.; Aristizabal-Ochoa, J. Dario
Abstract: A novel linear matrix method to analyze balanced and unbalanced adhesive joints is presented in this paper. The stiffness matrix, loading vector and transfer functions for the analysis of adhesive joints such as stiffened plate, single-strap and single-lap joints are derived in a classic manner. A matrix formulation is derived for a two-layer beam composed of two elements (adherends) and an adhesive. The proposed method takes into account the following effects: a) longitudinal and transversal relative displacements along the interface; b) the interaction between the normal and shear stresses; c) the coupling between the axial, bending and shear deformations in the adherends; and d) the transverse load applied on the two adherends. The expressions developed for the load vector are general for any type, or combination, of transverse load that fits a second-order polynomial curve, including uniformly distributed transverse load, trapezoidal and parabolic loads. The transfer functions necessary to determine the adhesive stresses, axial and shear forces, bending moments, deflections and rotations along the members are also presented in detail. Two comprehensive examples are presented to show the effectiveness and validity of the proposed method and corresponding equations.